ANALISIS PENGGUNAAN LPG TERHADAP PERFORMA DAN EMISI GAS BUANG PADA MOTOR BENSIN 125 CC - Triono, Bambang; M.Fansyah Ari (JURNAL ILMIAH TEKNIK INDUSTRI DAN INOVASI, 2024)
This study aims to analyze the effect of Liquefied Petroleum Gas (LPG) fuel on the performance (torque and power) and exhaust emissions of a 125 cc Supra X 125 motorcycle (2010 model). An experimental method was applied by testing the engine using two types of fuel, namely gasoline and LPG. The independent variable in this study is the type of fuel, while the dependent variables include torque, power, and exhaust emissions consisting of carbon monoxide (CO), hydrocarbons (HC), and carbon dioxide (CO₂). The tests were conducted at various engine speeds (RPM) using a dynamometer, while emission measurements were analyzed using a gas analyzer.The results show that LPG fuel produces slightly lower torque and power compared to gasoline, especially at low to medium engine speeds. This is attributed to differences in calorific value and air–fuel mixing characteristics. However, at higher engine speeds, LPG shows more stable performance. In terms of emissions, LPG significantly reduces CO and HC emissions, while CO₂ emissions slightly increase, indicating more complete combustion.It can be concluded that LPG has potential as a cleaner alternative fuel, despite a slight reduction in engine performance.